2022
DOI: 10.1111/jog.15486
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chromosomal microarray analysis and next‐generation sequencing to genetic diagnosis in fetuses with normal karyotype

Abstract: Aim:The aim of this study was to investigate the contribution of chromosomal microarray analysis (CMA) and next-generation sequencing (NGS) to genetic diagnosis in fetuses with normal karyotype who underwent invasive testing for different indications. Methods: The results of invasive genetic testing performed at a tertiary center between September 2020 and March 2022 were retrospectively analyzed. Indications for invasive tests were classified as fetal structural malformation, presence of soft markers, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
2
2
1
Order By: Relevance
“…It is surprising that the rates of TOPFA remained stable despite the improvement in diagnostic tools, which would logically lead to an expected increase in the identification of fetal abnormalities. CMA has now become the primary method for cytogenetic analysis in prenatal testing and has significantly enhanced diagnostic yield 8,11,28 . As expected we did observe an elevated identification of deletions, duplications, and single nucleotide variations as the indication for TOPFA, but without significantly affecting the overall number of pregnancy terminations.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is surprising that the rates of TOPFA remained stable despite the improvement in diagnostic tools, which would logically lead to an expected increase in the identification of fetal abnormalities. CMA has now become the primary method for cytogenetic analysis in prenatal testing and has significantly enhanced diagnostic yield 8,11,28 . As expected we did observe an elevated identification of deletions, duplications, and single nucleotide variations as the indication for TOPFA, but without significantly affecting the overall number of pregnancy terminations.…”
Section: Discussionsupporting
confidence: 84%
“…CMA has now become the primary method for cytogenetic analysis in prenatal testing and has significantly enhanced diagnostic yield. 8,11,28 As expected we did observe an elevated identification of deletions, duplications, and single nucleotide variations as the indication for TOPFA, but without significantly affecting the overall number of pregnancy terminations. -285…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although our study did not find any CNVs, studies have found significant CNVs on CMA in cases of AHNB (Gu et al, 2019; Zhang et al, 2021). CMA has also increased yield in euploid fetuses on karyotyping (Akalın et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These tests alone or in combination can identify an underlying genetic etiology in up to 75% of structurally abnormal fetuses, though still leaving cases without a diagnosis. 13 Research has examined the positive association between prenatal genetic counseling and uptake of diagnostic testing; 14 however, this has not been explored at the time of pregnancy termination for fetal indications that include suspected aneuploidy or congenital birth defects. 15,16 The purpose of this study was to identify predictors and utility of diagnostic genetic testing at the time of interruption of pregnancy.…”
mentioning
confidence: 99%